2021
DOI: 10.3390/ijerph18126655
|View full text |Cite
|
Sign up to set email alerts
|

Association between Health-Related Physical Fitness and Respiratory Diseases in Adolescents: An Age- and Gender-Matched Study

Abstract: The current study examined the differences in health-related physical fitness (HRPF), physical activity (PA), and sedentary behavior (SB) between adolescents with and without ongoing respiratory diseases (RD). This study’s participants were from 12 to 15 years old (7th–10th grade) in South Korea. Adolescents with RD were selected through RD-related questions (i.e., asthma, rhinitis, sinusitis, and bronchitis) (n = 139); in contrast, adolescents without RD, randomly selected from the general group, responded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The difference may be due to the diversity of gender and age distribution between the two studies. In Beijing, the proportion of older patients and cardiovascular problems was higher, and advanced age is well-known as a cardiovascular risk factor ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The difference may be due to the diversity of gender and age distribution between the two studies. In Beijing, the proportion of older patients and cardiovascular problems was higher, and advanced age is well-known as a cardiovascular risk factor ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physical fitness related to health occurs when physical activities are performed without significant fatigue (Fynmore, 1985). Elements of health-related physical fitness include cardiovascular endurance, muscle strength, muscle endurance, flexibility, and body composition (Blair et al, 2001;Nova, Risma;Syahrial, Bakhtiar;Umar;Fiky Zarya;Japhet, 2024;Park et al, 2021). On the other hand, elements of physical fitness related to sports skills include speed, power, balance, agility, coordination, and reaction speed (Corbin, 2000;Farley, Barrett, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been regarded as one of the human basic requirements. In addition, it serves as a powerful indicator of health among youth [ 5 ], and consists of five components, including cardiovascular endurance, muscular strength and endurance, flexibility, and body composition [ 6 , 7 ]. Accumulative evidence has suggested that a low level of health-related physical fitness is associated with premature mortality induced by various systems, such as cardiovascular, respiratory, and metabolic disorders [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%